Amino Acid Metabolism in Liver Mitochondria: From Homeostasis to Disease - Ranya Erdal; Kıvanç Birsoy; Gokhan Unlu (Metabolites)
Hepatic mitochondria play critical roles in sustaining systemic nutrient balance, nitrogen detoxification, and cellular bioenergetics. These functions depend on tightly regulated mitochondrial processes, including amino acid catabolism, ammonia clearance via the urea cycle, and transport through specialized solute carriers. Genetic disruptions in these pathways underlie a range of inborn errors of metabolism, often resulting in systemic toxicity and neurological dysfunction. Here, we review the physiological functions of hepatic mitochondrial amino acid metabolism, with a focus on subcellular compartmentalization, disease mechanisms, and therapeutic strategies. We discuss how emerging genetic and metabolic interventions—including dietary modulation, cofactor replacement, and gene therapy—are reshaping treatment of liver-based metabolic disorders. Understanding these pathways offers mechanistic insights into metabolic homeostasis and reveals actionable vulnerabilities in metabolic disease and cancer.